Bank Syariah di Indonesia: Analisis Pengaruh Rata-Rata Tingkat Bagi Hasil Deposito dan Rata-Rata Tingkat Suku Bunga Deposito Terhadap Jumlah Deposito dan Jumlah Nasabah Deposito Periode 2009-2014 - Aprilia Pratiwi; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aimed to determine the average profit-loss sharing level of deposit and the return level of deposit affect to total deposit and the quantity of Islamic banking customer in Indonesia, in time year 2009 until year 2014. The approach is a quantitative approach using VECM (Vector Error Correction Model) analytical techniques, to determine the effect of independent variable to dependent variable. The independent variable of this research is the average profit-loss sharing level of Islamic banking and the return level of deposit in conventional banking. While the dependent variable of this research is the total deposit and the quantity of Islamic banking customer in Indonesia. The result of this research showed that independent variable has a significant effect to total deposit in a long term, both simultaneous and partial. While in the quantity of customer, independent variable has no significant effect, both simultaneous and partial in a long term.